Heat transfer properties of laser assisted plasma processing - Parkins, Jonathon (Cranfield University, 2012)
Laser assisted plasma processing (LAPP) is a novel extension to already established Reactive Atom Plasma (RAP) processing for atmospheric pressure dry chemical etching of silicon based materials; this is mainly applied for optical uses. The development of the new technology involves the implementation of an additional laser energy beam to tune the thermal footprint of the hybrid tool. This will influence the temperature-dependent etching reaction. The aim of the project was to develop a model to predict the temperature footprint of components of the LAPP tool and assess the suitability of this model in simulating the thermal effects during an actual process. This was undertaken via two routes: model development and experimental temperature investigation. The two materials investigated were Corning Ultra Low Expansion glass (ULE) and also Silicon Carbide (SiC). The model was developed using Matlab from an established analytical method and evolved for LAPP use. An analytical method based on a Green’s function solution to the heat equation for a moving Gaussian heat source on a surface was chosen as it would be an adaptable and rapid alternative to costly experimental measurements for LAPP. Experimental temperature measurements were investigated using pyrometers, resistance temperature detectors and thermocouples. Typical LAPP process parameters were investigated for both a laser source and a RAP torch, and the temperature was measured. Additionally, surface reflectivity was measured for appropriate wavelengths for LAPP applications using a Fourier transform infrared spectrometer to determine the absorbed portion of laser energy. The experimental work conducted using RTDs found strong correlation with the modelling, with 63% of results matching within experimental error. The pyrometer measurements were less successfully replicated, the reason for which is expected to be the cooling of the substrate from its upper surface not being accounted for in the model. Overall trends of temperature rise decreasing with increasing feed speed or decreasing power were observed. Thermocouple characterisation of the RAP torch was approximated using the radiative model.